2003
DOI: 10.1207/s15327752jpa8103_08
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Private Self-Consciousness Scale: Role of Item Wording

Abstract: In 3 studies, I have tested the structure of different phrasing versions of the Private Self-Consciousness Scale (PrSC; Fenigstein, Scheier, & Buss, 1975) using exploratory and confirmatory factor-analytic methods and examined their predictive validity. For the original version of the PrSC, a 2-factorial model similar to Nystedt and Ljungberg's (2002) solution was found to best fit the data. When all scale items included extreme rate of occurrence words such as always, a single-factor solution emerged. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(61 reference statements)
1
6
0
2
Order By: Relevance
“…There are many demonstrations of how item wording substantially affects subsequent results (e.g., Sinclair & Tetrick, 2000;Torangeau & Rasinski, 1988), including evidence that more extreme and neutral scales in terms of items can yield dissimilar results (Ben-Artzi, 2003). Items used in scale construction must be evaluated individually to confirm that they reflect the construct in question.…”
Section: The Importance Of Item Wordingmentioning
confidence: 99%
“…There are many demonstrations of how item wording substantially affects subsequent results (e.g., Sinclair & Tetrick, 2000;Torangeau & Rasinski, 1988), including evidence that more extreme and neutral scales in terms of items can yield dissimilar results (Ben-Artzi, 2003). Items used in scale construction must be evaluated individually to confirm that they reflect the construct in question.…”
Section: The Importance Of Item Wordingmentioning
confidence: 99%
“…Many studies have criticized the psychometric qualities of the original scales, suggesting that the private self-consciousness scale should be split into two subfactors (Anderson et al, 1996, Ben-Artzi, 2003, Chang, 1998, Creed and Funder, 1998and Ruipérez and Belloch, 2003. One subfactor, known as self-reflection, reflects a maladaptive self-consciousness; the other, known as internal-state awareness, reflects an adaptive self-consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…The FSCS 32 is currently the most‐used measure for the assessment of self‐consciousness/self‐awareness 33 and has been found to be valid and reliable 32,34 . The FSCS comprises three subscales: private self‐consciousness, public self‐consciousness, and social anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…27 A study in dermatology outpatients 29 found it to have sensitivity and specificity of 79 and 78%, respectively, in detecting ''minor psychiatric disorder'', and it has been deemed to have ''extraordinary clinical utility'' in screening for psychiatric morbidity in dermatology patients. 31 The FSCS 32 is currently the most-used measure for the assessment of self-consciousness/self-awareness 33 and has been found to be valid and reliable. 32,34 The FSCS comprises three subscales: private self-consciousness, public selfconsciousness, and social anxiety.…”
Section: Methodsmentioning
confidence: 99%